Jelly making - Cunningham, Mamie Grace (My University, 1905)
Introduction: There are two kinds of food to which the term jelly is applied; first, that made by boiling fruit juices with sugar, and secondly, that made by adding gelatin, or similar substance, to fruit or vegetable juices. Only the former, that is, those made without the aid of special gelatinizing material, will be treated in this article. The experiments with jelly naturally come under three divisions. These are chemistry, horticulture and domestic science. Under chemistry comes the chemical alternations involved in the formation of jelly, the composition of the juices and jellies, the change made by the addition of sugar to fruit juices and experiments of similar nature. To the division of horticulture belongs the testing of different kinds and varieties of fruit to ascertain their value as jelly fruits. Such experiments as the method of preparing the fruit, the length of time of boiling, the addition of sugar and methods of keeping the jelly belong to the division of domestic science. Topics included under the head of chemistry and horticulture are touched upon in this treatise but those relating to domestic science form the principal part. The process of jelly making is a subject upon which very little has been written. Some of the experiment stations have made some tests in the work and all magazines and books on cooking contain recipes for jelly and possibly some few of them a few directions, but full discussions such as can be found on other topics in domestic science are very scarce. Most housewives who make good jelly do so through no skill they have acquired from books but from experience. However it must be admitted that the best instructor in the art of jelly making is experience. The kinds of fruit vary so widely in their jellying quality, and even the same varieties differ so because of the conditions under which they were picked, the stage of ripeness and similar reasons, that hard and fast rules cannot always be given. Yet there are many general rules and principals which should be followed and there is no reason why a house wife should not be acquainted with them.
Jelly experiments
Citation: Cunningham, Mamie Grace. Jelly making. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Calcium Salts; Organic Acids; Fruit Juice; Pectin; Coagulum; Theses